An Eco-Friendly Phosphogypsum-Based Cementitious Material: Performance Optimization and Enhancing Mechanisms - Wang, Ziyan; Shui, Zhonghe; Sun, Tao; Li, Zhiwei (Frontiers in Physics, 2022)
Little published data was effective to decrease the setting time and improve the strength development of phosphogypsum-based supersulphate cement (P-SSC) contained excess 40% phosphogypsum to achieve adequate field working and mechanical properties. This study tried to optimize the application performance of P-SSC by wet-grinding, of which the enhancement mechanism was discussed further. The wet-grinding mainly refined and dispersed the phosphogypsum with the large particle size, improving the formation of ettringite by increasing the supersaturation of phosphogypsum. However, the release of impurities prolonged the setting time of P-SSC pastes, leading to a lower early strength. Short-time wet-grinding destroyed the surface structure of slag with a small particle size, presenting a higher hydration degree. It seemed to have a more significant improvement of generated C-(A)-S-H gel, while treating P-SSC by wet-grinding had slight enhancement on strength development. Increasing the concentration of aluminate by adding active aluminium phases in this process promoted the generation rate of ettringite and weakened the negative effect of impurities release. therefore, a feasible and effective way to prepare P-SSC pastes was proposed to realise the large-scale application of phosphogypsum in the building materials industry.